Modifying lines-of-flight in the planning process for improved maintenance robustness - Lapp, Marcial; Cohn, Amy (Computers & operations research, 2012)
As a part of their planning process, airlines construct lines-of-flight ( LOFs ) – daily repeating sequences of flights, each of which will be flown by a single aircraft. In the week leading up to the actual day-of-operations, these LOFs are then assigned to specific aircraft ( tails), forming multi-day aircraft routings that in turn enable the scheduling of routine maintenance checks. Operational disruptions, however, can lead to deviations from these routings, which in turn disrupt the maintenance plan. The goal of our research is to improve the construction of LOFs so as to increase the likelihood of being able to recover from maintenance disruptions without costly over-the-day aircraft swaps. We present a new metric, maintenance reachability ( MR), which measures the robustness of a planned set of LOFs, and develop a mathematical programming approach to improving the MR of a given set of LOFs. We provide computational results based on data from a major U.S. carrier demonstrating that significant improvements in MR can be achieved with only a small number of changes to the original set of LOFs. Finally, we conclude by showing that even under imperfect input data, MR can be improved relative to a planned set of LOFs.